Cyclophosphamide‐induced Down‐Regulation of Uroplakin II in the Mouse Urinary Bladder Epithelium is Prevented by S‐Allyl Cysteine. Issue 6 (21st July 2016) - Abdi, Sayed Aliul Hasan; Najmi, Abul Kalam; Raisuddin, Sheikh
Abstract: The alkylating anticancer drug, cyclophosphamide (CP), induces a number of toxic effects including haemorrhagic cystitis (HC) in the urinary bladder. Uroplakins are unique urinary transmembrane proteins of urothelium, which may become potential targets of CP metabolites and reactive free radicals. Natural compounds, especially those rich in thiols, have shown protective effects against CP‐induced HC. In this study, we studied the modulatory effect of the thiol‐rich compound S ‐allyl cysteine (SAC) on the mRNA level of uroplakin II by real‐time polymerase chain reaction and expression of uroplakin II protein by immunoblotting. SAC (150 mg/kg) showed significant ( p < 0.001) protective effects against CP (200 mg/kg)‐induced alteration in mRNA level and protein expression of uroplakin II. SAC also protected animals from CP‐induced HC as assessed by gross morphological examination of urinary bladder. When compared with mercaptoethane sulphonic acid (mesna) (40 mg/kg), a known thiol‐rich drug used in clinical application, SAC was found to be more efficacious in affording protection in urinary bladder tissues. Role of uroplakins in CP‐induced urinary bladder toxicity has not been well investigated. This study demonstrated that uroplakins may be the potential target of toxic metabolites of CP and natural compounds such as SAC have the capacity to modulate their expression leading to reduced toxicity burden on the urinary bladder epithelium.